SUSTAINABLE PERFORMANCE: ENHANCING CI ENGINES WITH GREEN-SYNTHESIZED NANOPARTICLES AND BIODIESEL - Chaudhari, Kiran D.; Salunke, Nilesh P.; Diware, Vijay R.; Saner, Dr. Kapil; Suryavanshi, Vijay K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the potential of green-synthesized nanoparticles (NPs) doped with a 20% biodiesel blend to enhance the performance and emissions characteristics of a compression ignition (CI) engine. The green synthesis of NPs offers an environmentally friendly alternative to conventional methods, while the addition of biodiesel provides a renewable fuel source. Experimental trials were conducted using various concentrations of NP-doped biodiesel blends in a CI engine. Performance parameters such as brake specific fuel consumption (BSFC), brake thermal efficiency (BTE), and exhaust gas temperature (EGT) were measured. Additionally, emissions profiles, including smoke intensity, carbon monoxide (CO), oxides of nitrogen (NOx), and unburned hydrocarbons (HC), were analyzed. The results demonstrated that the incorporation of NP-doped biodiesel blends led to significant improvements in engine performance. A reduction in BSFC and an increase in BTE were observed, indicating enhanced fuel efficiency. Furthermore, the NP-doped blends contributed to a substantial decrease in smoke, NOx and other harmful emissions, suggesting a positive environmental impact. This research highlights the promising potential of green-synthesized NPs and biodiesel blends as a sustainable and efficient fuel alternative for CI engines.